Potential output in DSGE models - Igor Vetlov; Tibor Hlédik; Magnus Jonsson; Henrik Kucsera; Massimiliano Pisani (European Central Bank (ECB), 2011)
In view of the increasing use of Dynamic Stochastic General Equilibrium (DSGE) models in the macroeconomic projections and the policy process, this paper examines, both conceptually and empirically, alternative notions of potential output within DSGE models. Furthermore, it provides historical estimates of potential output/output gaps on the basis of selected DSGE models developed by the European System of Central Banks' staff. These estimates are compared to the corresponding estimates obtained applying more traditional methods. Finally, the paper assesses the usefulness of the DSGE model-based output gaps for gauging inflationary pressures.
Keywords: E32; E37; E52; 330; monetary policy; potential output; simulation and forecasting models